Early recognition socialization of stunting through educational counseling - Anang Satrio Utomo; Bagas Aryo Saloko (Universitas Pendidikan Indonesia, 2024)
The stunting rate in West Java is quite high even though each year there is a decrease in stunting cases. However, it is still targeted that there are no stunting cases in West Java or zero stunting. Therefore, community service activities focus on combating stunting with 3B (Wise Learning Together) in West Java, especially in the Subang area. The program carried out is by holding counseling activities in elementary schools with the target of early childhood participants. Counseling activities are carried out by utilizing poster learning media and games to create an interactive learning atmosphere. The practice of healthy lifestyle activities is also carried out to teach students the importance of having a healthy lifestyle. The service activities showed success in teaching stunting and its dangers to students in grades 3 and 4. They were given an understanding of nutritious foods that need to be consumed by children to prevent chronic nutritional diseases by utilizing poster media to attract interest. Game media was also used to determine students' understanding of the material after counseling. Students' understanding of stunting and its dangers increased after attending counseling, previously students did not know about stunting. Abstrak Angka stunting di Jawa Barat cukup tinggi meskipun tiap tahunnya mengalami penurunan kasus stunting. Namun, tetap saja kasus stunting di Jawa Barat ditargetkan tidak ditemukan atau zero stunting. Oleh karena itu, kegiatan pengabdian memfokuskan pada pemberatasan stunting dengan 3B (Bijak Belajar Bersama) di Jawa Barat, khususnya Daerah Subang. Program yang dilakukan yaitu dengan mengadakan kegiatan penyuluhan pada sekolah dasar dengan target patisipan anak usia dini. Kegiatan penyuluhan dilakukan dengan memanfaatkan media pembelajaran poster dan permainan untuk menciptakan suasana pembelajaran yang interaktif. Praktik kegiatan pola hidup sehat pun dilakukan untuk mengajarkan peserta didik pentingnya memiliki pola hidup sehat. Kegiatan pengabdian menunjukkan keberhasilan dalam mengajarkan stunting dan bahayanya pada peserta didik kelas 3 dan 4. Diberi pemahaman makanan bergizi yang perlu dikomsumsi oleh anak supaya mencegah penyakit gizi kronis dengan memanfaatkan media poster untuk menarik minat. Media permainan pun dilakukan untuk mengetahui pemahaman materi peserta didik setelah dilakukan penyuluhan. Pemahaman para peserta didik mengenai stunting dan bahayanya meningkatkan setelah mengikuti penyuluhan, sebelumnya peserta didik tidak mengetahui stunting sedikitpun. Kata Kunci: konseling stunting; pengabdian masyarakat; sosialisasi